Accelerated fracture healing in transgenic mice overexpressing an anabolic isoform of fibroblast growth factor 2. Issue 3 (20th January 2016) - Hurley, Marja M.; Adams, Douglas J.; Wang, Liping; Jiang, Xi; Burt, Patience Meo; Du, Erxia; Xiao, Liping
ABSTRACT: The effect of targeted expression of an anabolic isoform of basic fibroblast growth factor (FGF2) in osteoblastic lineage on tibial fracture healing was assessed in mice. Closed fracture of the tibiae was performed in Col3.6–18 kDa Fgf2 ‐IRES‐GFPsaph mice in which a 3.6 kb fragment of type I collagen promoter (Col3.6) drives the expression of only the 18 kD isoform of FGF2 (18 kDa Fgf2/ LMW) with green fluorescent protein‐sapphire (GFPsaph) as well as Vector mice (Col3.6‐IRES‐GFPsaph, Vector) that did not harbor the FGF2 transgene. Radiographic, micro‐CT, DEXA, and histologic analysis of fracture healing of tibiae harvested at 3, 10 and 20 days showed a smaller fracture callus but accelerated fracture healing in LMWTg compared with Vector mice. At post fracture day 3, FGF receptor 3 and Sox 9 mRNA were significantly increased in LMWTg compared with Vector. Accelerated fracture healing was associated with higher FGF receptor 1, platelet derived growth factors B, C, and D, type X collagen, vascular endothelial cell growth factor, matrix metalloproteinase 9, tartrate resistant acid phosphatase, cathepsin K, runt‐related transcription factor‐2, Osterix and Osteocalcin and lower Sox9, and type II collagen expression at 10 days post fracture. We postulate that overexpression of LMW FGF2 accelerated the fracture healing process due to its effects on factors that are important in chondrocyte and osteoblast differentiation and vascular invasion. J. Cell. Biochem. 117: 599–611, 2016. © 2015 Wiley Periodicals, Inc.